Respuesta :

Step-by-step explanation:

pls click on the pic for full answers

Ver imagen nandhinielango82

Let's solve this step-by-step. Here it is.

5x²+7x=x²+2

Step 1: subtract 2 from both the left and right side.

5x²+7x-2=x²+2-2

Simplify.

5x²+7x-2=x²

Step 2: subtract x² from each side.

5x²-x²+7x-2=x²-x²

Simplify.

4x²+7x-2=0

Step 3: solve using the quadratic formula.

[tex]x_{1,\:2}=\frac{-7\pm \sqrt{7^2-4\cdot \:4\left(-2\right)}}{2\cdot \:4}[/tex]

[tex]x_1=\frac{-7+9}{2\cdot \:4},\:x_2=\frac{-7-9}{2\cdot \:4}[/tex]

[tex]x=\frac{1}{4},\:x=-2[/tex]

Hope this helps!

Step 2: Factor the left side of the equation.